2022
DOI: 10.1108/ijopm-04-2022-0265
|View full text |Cite
|
Sign up to set email alerts
|

Actions speak louder than words? The impact of subjective norms in the supply chain on green innovation

Abstract: PurposeAdopting the theory of planned behavior, this study attempts to investigate how subjective norms in the supply chain influence a firm's green innovation and how such influences are contingent upon the firm's internal and external factors (i.e. flexibility orientation and environmental dynamism). Two types of subjective norms are examined, i.e. injunctive norms (what supply chain partners say) and descriptive norms (what supply chain partners do).Design/methodology/approachUsing survey data of 178 Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 88 publications
3
20
1
3
Order By: Relevance
“…Conversely, if there is no perceived social pressure or norm to watch a particular video, an individual may be less likely to watch it. This finding also matched the results obtained by previous studies that also found the significance of subjective norms in determining people's intention and actual behavior (Nguyen et al, 2023;Abd-Mutalib et al, 2023;Shou et al, 2022;Balikcioglu et al, 2022;Nair, 2021;Ashraf et al, 2019;Wong et al, 2020;Agbetunde et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, if there is no perceived social pressure or norm to watch a particular video, an individual may be less likely to watch it. This finding also matched the results obtained by previous studies that also found the significance of subjective norms in determining people's intention and actual behavior (Nguyen et al, 2023;Abd-Mutalib et al, 2023;Shou et al, 2022;Balikcioglu et al, 2022;Nair, 2021;Ashraf et al, 2019;Wong et al, 2020;Agbetunde et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, firms will encourage different departments to work together and collaborate with customers to achieve process enhancement. Second, the wide adoption of sustainable shipping makes the firm consider such practice is necessary for it to sustain survival or growth (Shou et al, 2023), which will motivate the firm to operate in the same manner. Specifically, strong descriptive norms can serve as a pressure for shipping firms to utilize cross-functional and customer coordination to further drive DT-empowered sustainable shipping to keep themselves from lagging behind, or, better yet, outperforming their competitors.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…For instance, in the face of digital organizational change, people-oriented leadership behavior enables employees to transition this change more smoothly, reducing their emotional resistance and improving innovation performance. In addition, in the research related to corporate sustainability, it is also found that the individual behaviors and normative cognition of leaders are also important drivers of green behavior in organizations (Shou et al. , 2022; Xing et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish the theoretical underpinning of this study, we mobilized the theory of planned behavior (TPB) (Ajzen, 1991) and the entrepreneurial event model (Shapero & Sokol, 1982). These theoretical backgrounds received prominence and credibility to explain the formation of intention throughout many research areas, such as technology acceptance (e.g., Fink et al, 2022;Marangunić & Granić, 2015), consumer services (e.g., Paul et al, 2016;Timpanaro & Cascone, 2022), supply chain management (e.g., Kamble et al, 2019;Shou et al, 2022), family business (e.g., Graves et al, 2022;Singh et al, 2021), product innovation (e.g., Kim et al, 2019;Tóth et al, 2020), small business (e.g., Harrison et al, 1997;Sandhu & El-Gohary, 2022), and absorptive capacity (e.g., Chao & Yu, 2022;Mo et al, 2022). More interestingly, these foundations have recently emerged as a cornerstone in investigating the COVID-19 influence on intention research across several fields, including psychology (e.g., Islam et al, 2020;Shanka & Gebremariam Kotecho, 2021);tourism (e.g., Jeon et al, 2022;Xu et al, 2022); sustainability (e.g., Cahigas et al, 2022;Seong et al, 2021); and, more importantly, entrepreneurship (e.g., Lang et al, 2022;Li et al, 2022;Seah, 2021).…”
Section: Theoretical Underpinningmentioning
confidence: 99%